2006
DOI: 10.1111/j.1365-2753.2006.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival from breast cancer: the experience of patients at South Australian teaching hospitals between 1977 and 2003

Abstract: Survivals appear to be increasing and treatment trends are broadly consistent with guideline directions, and the earlier research on which these recommendations were based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Multiple studies from other countries have shown age at diagnosis to be an independent risk factor for breast cancer mortality (Adami et al, ; Anders et al, ; Bastiaannet et al, ; Eaker, Dickman, Bergkvist, & Holmberg, ; Fredholm et al, ). This review consistently demonstrated that younger and older women in the < 40 and > 70 age group, respectively, were at higher risk of breast cancer mortality (Clayforth et al, ; Dasgupta et al, ; Luke et al, ; Roder, Silva et al, ; Roder et al, ; Roder, Webster et al, ; Supramaniam et al, ). Furthermore, despite this being an independent risk factor, it is often compounded by other factors which also contribute to increased breast cancer mortality.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Multiple studies from other countries have shown age at diagnosis to be an independent risk factor for breast cancer mortality (Adami et al, ; Anders et al, ; Bastiaannet et al, ; Eaker, Dickman, Bergkvist, & Holmberg, ; Fredholm et al, ). This review consistently demonstrated that younger and older women in the < 40 and > 70 age group, respectively, were at higher risk of breast cancer mortality (Clayforth et al, ; Dasgupta et al, ; Luke et al, ; Roder, Silva et al, ; Roder et al, ; Roder, Webster et al, ; Supramaniam et al, ). Furthermore, despite this being an independent risk factor, it is often compounded by other factors which also contribute to increased breast cancer mortality.…”
Section: Discussionmentioning
confidence: 87%
“…Higher grade tumours were consistently associated with higher risk of mortality (Craft et al, ; Lim et al, ; Luke et al, ; Roder, Silva et al, ; Roder et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Data linkage of extracted SACCR and BreastScreen South Australia data was used to identify histories of BreastScreen participation among women aged 50‐69 years at invasive breast cancer diagnosis . This was classified as no participation or participation last occurring <6 months, 6‐24 months, or 25+ months prior to breast cancer diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Person characteristics were analyzed, depending on their distribution, as age at diagnosis (four 5‐year ordinal categories); SEIFA socioeconomic disadvantage (4 ordinal categories), geographic remoteness (3 ordinal categories), Local Health Network (4 nominal categories), and Medicare Local (5 nominal categories). Tumor characteristics, including histology, TNM (UICC 7th Revision) stage, diameter, nodal status, differentiation, and estrogen and progesterone receptor status were classified as shown in Table …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation